Barcamps or unconferences as an emerging paradigm in medical education: insights from a pilot and feasibility mixed methods study - Romeike, Bernd F. M.; Lang, Johannes; Stosch, Christoph; Moritz, Sören; Behrends, Marianne; Lemos, Martin; Mink, Johanna; Tolks, Daniel (PLOS ONE, 2024)
Medical education is experiencing a paradigm shift towards more interactive and collaborative pedagogical approaches. Barcamps, also known as unconferences, offer an interactive, participant-driven learning approach. This study aims to evaluate the feasibility of using barcamps as an educational model in medical education. Furthermore, the possibility of establishing barcamps in medical education as a pedagogical tool is discussed. The study integrates two evaluations to achieve a multifaceted understanding: a pilot study conducted in 2022 and a subsequent feasibility study in 2023. Participation in the barcamps and their evaluations was voluntary. We combined quantitative data, primarily from post-event evaluations, and qualitative data from open-ended survey questions. These methods were designed to capture a broad range of participant experiences and perceptions. The pilot study in 2022 included 11 participants and produced a response rate for the evaluations. The feasibility study in 2023 had 34 participants but a lower evaluation response rate of 53%. Both barcamps were generally positively evaluated by the participants, indicating a high level of satisfaction and perceived value. Regarding the active participation of participants, the wide range of presented topics highlights the adaptability and flexibility of the barcamp model. Attendees at the pilot mentioned a significantly higher previous experience with barcamps. The study suggests that barcamps are generally well received as an interactive and collaborative educational tool in medical education, reflected by high participant evaluation scores. The wide range of topics presented and discussed indicates that barcamps can accommodate diverse educational needs and interests. However, the study also identified areas for improvement, most notably in the structure of topic plans and the overall learning environment. Finally, the principals for barcamps might adapt to other educational methods by adding more interaction, choice, collaboration, communication, critical thinking, creativity, and caring to the learning process.
Gesehen am 05.11.2024